Sensitivity of an improved method for post-life laboratory diagnosis of chicken eimeriosis - V. Hodyna (Ukrainian Journal of Veterinary and Agricultural Sciences)
Poultry farming is vital in providing the population with high-quality food products – eggs and poultry meat. Poultry farming is characterized by rapid livestock reproduction rates, the lowest per unit of output compared to other livestock industries. To maintain high economic performance and produce high-quality products, it is necessary to ensure veterinary well-being concerning invasive diseases. The dangerous protozoan disease eimeriosis cause significant financial losses, high mortality of young poultry, decreased chicken productivity, and the quality of products from sick birds. The work aimed to improve and determine the sensitivity of the method of post-life laboratory diagnostics of eimeriosis in chickens. The proposed useful model relates to veterinary medicine, namely, veterinary parasitology, to methods of ovoscopic studies of chicken droppings, particularly a quantitative method for detecting eimeriosis oocysts. It was found that when examining chicken droppings for the presence of Eimeria oocysts, the most effective method was the improved method, which is based on using a combined hypertonic solution with a high specific gravity and well-defined coagulation properties. When using it, it was possible to detect the most significant number of oocysts – 1285.20 oocysts/g of droppings, which was 8.24 % more compared to the analog method (the method of quantitative coproscopic diagnostics of nematodoses of the digestive tract of ruminants) and 33.17 % (P < 0.01) – compared to the known method (Stall's method). Also, the improved method is the most optimal regarding the number of positive samples, the number of detected invasive elements in 1 g of droppings, and the coagulation ability of the flotation solution concerning undigested feed residues detected during microscopy. The obtained research results allow us to recommend implementing the proposed method for quantitative detection of Eimeria sp. oocysts in chicken droppings for effective,  sensitive, and timely laboratory diagnostics of Eimeria sp.